PENGARUH AUDIT FEE, OPINI GOING CONCERN, FINANCIAL DISTRESS, UKURAN PERUSAHAAN, UKURAN KAP PADA PERGANTIAN AUDITOR - Wijaya, Edwin; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
The purpose of this study was to determine the effect of audit fee, going concern opinion, financial distress, the size of the company and the size of the firm at the turn of the auditor. The type of data used is quantitative data in the form of financial statements of companies manufacturing the period 2008-2013 listed in Indonesia Stock Exchange. The Source of data is secondary data. The Samples using is purposive sampling method, and the number of samples is 96 companies. Data were analyzed using logistic regression analysis, because the dependent variable using dummy variables. The results showed the audit fee and the going concern opinion affect the auditor turnover. While financial distress, the size of the company and the size of KAP has no effect on the change of auditor
Keywords: Audit Fee, Going Concern Opinion, Financial Distress, Company Size, Size KAP